Avaliação clínica e neuropsicológica da estimulação cerebral profunda associada a intervenção cognitiva no tratamento da doença de Alzheimer: relato de caso - Souza, Rodrigo Marmo da Costa e (2018)
Recent studies have identified an association between memory deficits and defects of the integrated neuronal cortical areas known collectively as the default mode network. It is conceivable that the amyloid deposition or other molecular abnormalities seen in patients with Alzheimer’s disease may interfere with this network and disrupt neuronal circuits beyond the localized brain areas. Therefore, Alzheimer’s disease may be both a degenerative disease and a broader system-level disorder affecting integrated neuronal pathways involved in memory. In this paper, we reported a case report of invasive neuromodulation for Alzheimer disease describe the rationale and provide some evidence to support the study of deep brain stimulation of the hippocampal fornix as a novel treatment to improve neuronal circuitry within these integrated networks and thereby sustain memory function in early Alzheimer’s disease.